Interdisciplinarity in practice: Challenges and benefits for privacy research. Issue 6 (December 2017) - Métayer, Daniel Le; Bossuet, Mathias; Coudert, Fanny; Gayrel, Claire; Jaime, Francisco; Jouvray, Christophe; Kung, Antonio; Ma, Zhendong; Maña, Antonio
Abstract: The goal of this paper is to draw the lessons learned from a project that involved security systems engineers, computer scientists, lawyers and social scientists. Since one of the goals of the project was to propose actual solutions following the privacy by design approach, its aim was to go beyond multidisciplinarity and build on the variety of expertise available in the consortium to follow a true interdisciplinary approach. We present the challenges before describing the solutions adopted by the project to meet them and the outcomes and benefits of the approach. We conclude with some lessons to be drawn from this experience and recommendations for future interdisciplinary projects.